Bladder cancer patients have increased NETosis and impaired DNaseI-mediated NET degradation that can be therapeutically restored in vitro - Herranz, Raquel; Oto, Julia; Hueso, Marta; Plana, Emma; Cana, Fernando; Castaño, María; Cordón, Lourdes; Ramos-Soler, David; Bonanad, Santiago; Vera-Donoso, César D.; Martínez-Sarmiento, Manuel; Medina, Pilar (Frontiers in Immunology, 2023)
Background Neutrophils, key players of the immune system, also promote tumor development through the formation of neutrophil extracellular traps (NETs) in a process called NETosis. NETs are extracellular networks of DNA, histones and cytoplasmic and granular proteins (calprotectin, myeloperoxidase, elastase, etc.) released by neutrophils upon activation. NETs regulate tumor growth while promoting angiogenesis and invasiveness, and tumor cells also stimulate NETosis. Although NETosis seems to be increased in cancer patients, an increase of NETs in plasma may also be mediated by an impaired degradation by plasma DNaseI, as evidenced in several immunological disorders like lupus nephritis. However, this has never been evidenced in bladder cancer (BC) patients. Herein, we aimed to evaluate the occurrence of increased NETosis in plasma and tumor tissue of BC patients, to ascertain whether it is mediated by a reduced DNaseI activity and degradation, and to in vitro explore novel therapeutic interventions. Methods We recruited 71 BC patients from whom we obtained a plasma sample before surgery and a formalin-fixed paraffin embedded tumor tissue sample, and 64 age- and sex-matched healthy controls from whom we obtained a plasma sample. We measured NETs markers (cell-free fDNA, calprotectin, nucleosomes and neutrophil elastase) and the DNaseI activity in plasma with specific assays. We also measured NETs markers in BC tissue by immunofluorescence. Finally, we evaluated the ability of BC and control plasma to degrade in vitro-generated NETs, and evaluated the performance of the approved recombinant human DNaseI (rhDNaseI, Dornase alfa, Pulmozyme®, Roche) to restore the NET-degradation ability of plasma. In vitro experiments were performed in triplicate. Statistical analysis was conducted with Graphpad (v.8.0.1). Results NETosis occurs in BC tissue, more profusely in the muscle-invasive subtype (P<0.01), that with the worst prognosis. Compared to controls, BC patients had increased NETosis and a reduced DNaseI activity in plasma (P<0.0001), which leads to an impairment to degrade NETs (P<0.0001). Remarkably, this can be therapeutically restored with rhDNaseI to the level of healthy controls. Conclusion To the best of our knowledge, this is the first report demonstrating that BC patients have an increased NETosis systemically and in the tumor microenvironment, in part caused by an impaired DNaseI-mediated NET degradation. Remarkably, this defect can be therapeutically restored in vitro with the approved Dornase alfa, thus Pulmozyme® could become a potential therapeutic tool to locally reduce BC progression.